Chasing the dream—defying the odds: exploring the professional identity development of women in comedy - Cunningham, G (2021)
Although in today’s world of work “the repertoire of potential professional identities [individuals] can envision for themselves seems limitless” (Obodaru, 2017: 523), our understanding of professional identity development is limited when it comes to those who attempt to defy the odds in who they become in their careers. This thesis aims to understand the professional identity development process for individuals with odds-defying aspirations—hoped-for professional identities that, by their own estimation, seem unlikely to come about. Using in-depth interviews with aspiring professional comedians who also ‘happen to be women’ (Kirkman, 2016: 220), I develop a grounded theoretical model showing how odds-defying aspirers recalibrate their ideas regarding what is possible in the world of work, regarding what it means to succeed in achieving their aspirations, and regarding what is at stake in their decision to give up or go on in pursuing their odds-defying aspirations. These changes to their aspirational assumptions are brought about through the process of enacting their desired professional identities and receiving and managing identity feedback—efforts that require them to carefully navigate the competing identity threats of trying and failing or else of failing to try, as well as the steep risks and costs inherent in attempting to achieve their odds-defying aspirations. These developmental efforts gradually enable individuals to alter their regulatory focus and to build up their motivational resolve—moving away from focusing on preventing the loss of their nascent professional identity to focusing on promoting its growth and overcoming motivational precarity with motivational resilience. The findings highlight how this professional identity development process is recursive and circular, often requiring odds-defying aspirers to repeat these efforts throughout their careers. This research contributes to the literatures surrounding identity threat and identity play in professional identity development and provides practical insights into the lived experiences of odds-defying aspirers.